Structural Brain Abnormalities in Successfully Treated HIV Infection: Associations With Disease and Cerebrospinal Fluid Biomarkers. (24th October 2017) - van Zoest, Rosan A; Underwood, Jonathan; De Francesco, Davide; Sabin, Caroline A; Cole, James H; Wit, Ferdinand W; Caan, Matthan W A; Kootstra, Neeltje A; Fuchs, Dietmar; Zetterberg, Henrik; Majoie, Charles B L M; Portegies, Peter; et al.
Abstract : Lower gray matter volume and white matter microstructural abnormalities in persons living with human immunodeficiency and receiving suppressive combination antiretroviral therapy likely reflect historical injury that occurred during untreated infection, as well as a more general influence of systemic factors, such as hypertension and ongoing neuroinflammation. Abstract: Background: Brain structural abnormalities have been reported in persons living with human immunodeficiency virus (HIV; PLWH) who are receiving suppressive combination antiretroviral therapy (cART), but their pathophysiology remains unclear. Methods: We investigated factors associated with brain tissue volumes and white matter microstructure (fractional anisotropy) in 134 PLWH receiving suppressive cART and 79 comparable HIV-negative controls, aged ≥45 years, from the Comorbidity in Relation to AIDS cohort, using multimodal neuroimaging and cerebrospinal fluid biomarkers. Results: Compared with controls, PLWH had lower gray matter volumes (−13.7 mL; 95% confidence interval, −25.1 to −2.2) and fractional anisotropy (−0.0073; 95% confidence interval, −.012 to −.0024), with the largest differences observed in those with prior clinical AIDS. Hypertension and the soluble CD14 concentration in cerebrospinal fluid were associated with lower fractional anisotropy. These associations were independent of HIV serostatus ( P interaction = .32 and P interaction = .59, respectively) and did not explain the greater abnormalities in brain structure in relation to HIV infection. Conclusions: The presence of lower gray matter volumes and more white matter microstructural abnormalities in well-treated PLWH partly reflect a combination of historical effects of AIDS, as well as the more general influence of systemic factors, such as hypertension and ongoing neuroinflammation. Additional mechanisms explaining the accentuation of brain structure abnormalities in treated HIV infection remain to be identified.